ISLAMIC LEGAL PROTECTION FOR CRYPTO INVESTORS: A JURIDICAL ANALYSIS OF DIGITAL CRIMES IN VIRTUAL CURRENCY TRANSACTIONS - Jaya Darmawan; Husin Ritonga; Abdul Halim (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze and formulate a concept of Islamic legal protection for crypto investors in responding to the dynamics of digital crimes within virtual currency transactions. Departing from the rapid development of blockchain technology and the recognition of crypto assets as tradable commodities in Indonesia, this research identifies a normative ambiguity between positive law and religious fatwas, particularly concerning the permissibility and legal legitimacy of cryptocurrencies from a sharia perspective. The inherent characteristics of crypto assets-namely volatility, speculative tendencies, and vulnerability to digital crimes such as hacking, fraud, market manipulation, and money laundering-generate significant risks for Muslim investors. Within the framework of fiqh al-muʿāmalāt and maqāṣid al-sharīʿah, especially the principle of ḥifẓ al-māl (protection of wealth), this study asserts that investor protection constitutes not merely a regulatory necessity but an integral dimension of the higher objectives of Islamic law in safeguarding justice, transparency, and economic welfare. Methodologically, this research employs a normative-maqāṣidī approach through an interdisciplinary analysis integrating Islamic jurisprudence, national positive law, and the study of digital financial technology. The focus of the inquiry is directed toward identifying the typologies of digital crimes within the crypto ecosystem, evaluating the effectiveness of national regulations and religious fatwas, and formulating a model of Islamic legal protection that is preventive, corrective, and educational in nature. The expected outcome of this dissertation is the construction of a conceptual framework of ḥimāyah al-mustatsmir (investor protection) grounded in maqāṣid al-sharīʿah, adaptive to the digital era, and strengthened through synergy among the state, financial authorities, and fatwa institutions. Accordingly, this study contributes not only to the advancement of contemporary fiqh al-muʿāmalāt discourse but also offers an applicable normative framework for the development of a secure, equitable, and sustainable sharia-based digital economic system.